Analysis of Humor on Cartoon Comics "Be Like Bro": Pragmatics Study - Anindita Dewangga Puri; FX. Risang Baskara (Journal of Pragmatics Research, 2019)
This article aims to identify the types of violation of conversational maxims created by cartoon comic entitled “Be Like Bro” in the English version and also to describe how the humorous situation can be created from those violations. There are two findings in this research. First, those six data show that there is a violation of conversational maxims, which are the maxim of quantity, the maxim of relevance, and the maxim of manner. Those six data also show that the humorous situation is creating by incongruent meaning in the conversation and releasing the feeling. Keywords: humor, cooperative principles, context, pragmatics